Optimización del sistema de explotación para arcillas en el área minera Alfadomus 1, parroquia Taquil, cantón Loja, provincia de Loja. - Villamarín Jaramillo, María Luisa (2011)
The clay exploded in the mining area Alfadomus 1 is a superficial deposit which is distributed in layers along the location. Their origin is related to the physical decomposition and chemistry of the metamorphic rocks as: schists, lines, slates, existent in the area, belonging to the Series Zamora; he/she has the characteristic of being a meager clay, rich in row, with contained first floor of quartz, capable to be used in the industry of the ceramic. According to the Calculation of Reservations carried out through the Method of Parallel Cortes, they give us as a result 181863.75 Rhyme of Probable Reservations, 529200 Rhyme of Possible Reservations and 396900 Rhyme of Probable Reservations, with a time of Life 12 years old, carrying out a production daily 75.75 m3 (113.62 Rhyme), in days of work of 8 daily hours and of 11 days a month. The project is a model of economically sustainable and environmentally sustainable exploitation. For the geologic and technical conditions miner of the location and the little existent overload is considered to exploit the mineral to open sky. According to the professor's classification E.F SHESHKO will be carried out it under the denominated SYSTEM OF EXPLOITATION TO OPEN SKY WHEN THE DISPLACEMENT OF THE STERILE one TO THE ESCOMBRERA doesn't HAVE MEANING. The same one that will allow us to optimize the production, arriving to a production of 10000 m3 a year. Regarding the atmosphere he/she is carried out a plan of environmental handling, the same one that establishes the actions that are required to prevent, to mitigate, to control, to compensate and to correct the possible effects or impacts environmental negatives caused in the development of the present project.